ANALISIS PERENCANAAN DAN PENGENDALIAN PERSEDIAAN KEBUTUHAN TEMBAKAU DI INDONESIA - Syarif Hidayatulloh; Arief Budiman, Paduloh (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Tobacco is one of the cash crops that can be used as raw material in smoking activities and has many risks. In Indonesia, it is one of the largest tobacco producers and consumers in the world. In that case, the government made a statement as a support for the fulfillment of tobacco needs, with the aim that there is no excessive amount of inventory or shortage, so as not to harm a company. In this study, quantitative descriptive methods were used, in the calculation using forecasting with an EOQ approach and the help of an R Studio application / software. The result obtained is the maximum supply that can be managed with the lowest maximum supply is 4,188,968,000 / kg, while for the maximum supply the largest is 13,508,795,487 / kg. then the total cost of supplies is IDR 3,665,652,167,548